Technical report on the methodological approach used for the assessment of the control measures for Category A diseases in the context of the new Animal Health Law. Issue 12 (14th December 2020) - ,; Alvarez, Julio; Roberts, Helen Clare; Stahl, Karl; Viltrop, Arvo; Clercq, Kris De; Klement, Eyal; Stegeman, Jan Arend; Gubbins, Simon; Antoniou, Sotiria‐Eleni; Zancanaro, Gabriele; Aznar, Inma
Abstract : The purpose of this technical report is to present the methodology that will be implemented to address the terms of reference of a mandate received from the European Commission (EC). This mandate requests EFSA to assess the effectiveness of some of the control measures related to Category 'A' diseases. More specifically, in this report EFSA illustrates the methodology to assess the following features: i) the sampling of animals and establishments for the detection of category 'A' diseases in terrestrial animals; ii) the monitoring period; and iii) the minimum radius of restricted zones and duration of the disease control measures in restricted zones. The first step was to understand in detail the request of the EC and the outcome of this exercise is reported in the sections dedicated to the interpretation of the terms of reference. For the identification of the most suitable methodology, specific scenarios were identified, for each measure, to ensure that the approach was able to cover as many situations as possible in the field. Once the approach was identified, it was possible to define the data needs and the potential sources of information. Extensive literature search appeared to be essential to retrieve some of the necessary inputs for some diseases and for some important parameters; for this reason, and in the interest of time, EFSA procured this work by means of a public call. In case the scientific literature will not offer the required information, expert knowledge elicitation will serve the purpose. A section was dedicated to the assessment of the uncertainty. In conclusion, this work represents the general methodological framework underpinning the scientific opinions that will be issued for each category 'A' disease. Any unavoidable deviation from the approach as described here will be duly documented in the scientific opinions